2022
DOI: 10.1007/s10896-022-00446-x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Abuse: A Qualitative Exploration of UK Military Personnel and Civilian Partner Experiences

Abstract: Purpose The prevalence of Intimate Partner Violence and Abuse (IPVA) perpetration and victimisation has been found to be higher in serving and ex-serving military samples compared to civilians. Despite this, there is a lack of qualitative research exploring the IPVA experiences of couples in which one or both partners are serving or have served in the military. This qualitative study aimed to explore IPVA experiences within the UK military community from the perspective of serving and ex-serving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…This infliction of pain on the spouses made many female participants to have fear in their own homes and reduced their decision-making autonomy on many aspects that affected their wellbeing and that of their family. The finding resonates with partner experiences of IPV perpetrated by military personnel found in other studies (Lane et al, 2022;Lopez, 2022;Kwan et al, 2020). The study also revealed that participants admitted experiencing abusive sexual activities (sexual violence) from their military spouses that aroused feelings of rage and betrayal which others found hard to overcome.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This infliction of pain on the spouses made many female participants to have fear in their own homes and reduced their decision-making autonomy on many aspects that affected their wellbeing and that of their family. The finding resonates with partner experiences of IPV perpetrated by military personnel found in other studies (Lane et al, 2022;Lopez, 2022;Kwan et al, 2020). The study also revealed that participants admitted experiencing abusive sexual activities (sexual violence) from their military spouses that aroused feelings of rage and betrayal which others found hard to overcome.…”
Section: Discussionsupporting
confidence: 86%
“…On the contrary, Becker et al, (2021) echoed that IPV arose out of structural and patriarchal systems partners have been subjected to. Equally, Lane et al, (2022) study established that military personnel perpetuated IPV mainly to assert power and control over their partners. However, the study exposed that regardless of the cause of violence, it still attracted relatively the same nature of violence.…”
Section: Discussionmentioning
confidence: 99%